Can Financial Incentives Reduce the Baby Gap? Evidence from a Reform in Maternity Leave Benefits - Anna Christina Raute (Center for Economic Studies and ifo Institute (CESifo), 2017)
To assess whether earnings-dependent maternity leave positively impacts fertility and narrows the baby gap between high educated (high earning) and low educated (low earning) women, I exploit a major maternity leave benefit reform in Germany that considerably increases the financial incentives for higher educated and higher earning women to have a child. In particular, I use the large differential changes in maternity leave benefits across education and income groups to estimate the effects on fertility up to 5 years post reform. In addition to demonstrating an up to 22% increase in the fertility of tertiary educated versus low educated women, I find a positive, statistically significant effect of increased benefits on fertility, driven mainly by women at the middle and upper end of the education and income distributions. Overall, the results suggest that earnings-dependent maternity leave benefits, which compensate women commensurate with their opportunity cost of childbearing, could successfully reduce the fertility rate disparity related to mothers' education and earnings.
Keywords: J13; J16; J18; 330; fertility; fertility gaps; paid maternity leave